The dry eye syndrome in children with juvenile idiopatic arthritis - Lipiec, Ewa; Grałek, Mirosława; Niwald, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The aim of the study was to evaluate the dry eye syndrome in children with juvenile idiopathic arthritis (JIA), and its relation to the immunological markers of the JIA (antynuclear antybodies ANA and rheumatoid factor RF). Material and methods: The study included 62 children with JIA. The age of patients during the first ophthalmic examination ranged from 9 to 18 years (62 children). A control group consisted of 49 healthy children. The time of observation was 18 months during which the children and adolescents were subjected to complex ophthalmic examinations (including a history of eye discomfort and Schirmer and BUT tests), in the intervals of 9 months. The diagnosis towards dry eye syndrome was made (including a history of eye discomfort and Schirmer and BUT tests). Results: The majority of children with JIA complained of discomfort in the eyes. The difference appeared to be statistically significant between the group of children with JIA and the control group in the range of 5 features. The results of Schirmer test were found to be inadequate in 7 children (13%) and of BUT test in 9 children (15%). In total, inadequate results of Schirmer and/or BUT tests and a high score of discomfort evaluation were detected in 11 patients (17.7%). Conclusions: 1. The dry eye syndrome may occur in the course of JIA in children without any distinct clinical signs, resulting in subjective symptoms and decreasing the quality of life. 2. No correlation between immunological markers of the JIA and ocular changes was observed.